Comparison of the effectiven ess of emotion-oriented couple therapy and couple therapy based on acceptance and commitment on spiritual indicators (patience and forgiveness) in couples affected by extramarital relationships - Keyhan, Firoozeh; Ghanifar, Mohammad Hassan; Ahi, Qasem (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to compare the effectiveness of emotion-oriented couple therapy and couple therapy based on acceptance and commitment on spiritual indicators (patience and forgiveness) in couples affected by extramarital relationships. Methods: The present study was a pre-test-post-test and follow-up field with applied and experimental designs. The statistical population studied in this study included all couples affected by extramarital affairs who referred to counseling centers in Tehran in 2021, from which 60 people were selected by available sampling method and in three groups. Emotion-based couple therapy, acceptance and commitment-based couple therapy, and a control group (20 people in each group) were assigned. Data were obtained using the Forgiveness Questionnaire Ray, Loyaduno, Flock, Alzieowski, Him and Madia (2001), and the Patience Questionnaire Khormai (2009). Acceptance and commitment therapy based on the McKay et al. (2012) package and the emotion-based couple therapy protocol Johnson (2004) were administered in ten 90-minute sessions weekly. The control group did not receive treatment and was placed on a waiting list. For inferential analysis, repeated measures analysis of variance and SPSS.22 software were used. Results: The results showed that there was a significant difference between the three groups of emotion-oriented couple therapy, couple therapy based on acceptance and commitment and the control group on the spiritual indices of patience (F=71.59, P<0.001) and forgiveness (F= 136.80, P<0.001). There is a statistical opinion and forgiveness and patience in the acceptance and commitment treatment group at the end of the post-test were higher than the excited couple therapy group and the control group (p<0.01). Conclusion: It can be concluded that in terms of effectiveness, acceptance and commitment treatment had the greatest impact on improving the variables of forgiveness and patience.